Feasibility study of sports investment projects for small and medium enterprises in Algeria- A field study for the directorates of youth and sports - Chlef - Medea - Setif - nhaoua, louniss; Bourzama, Djamal; abbess, Amira (sports creativity, 2025)
This study examined the feasibility study of sports investment projects for (PME PMI) in Algeria; which maybe became a new trend approach theory on the economics of sport, and the economic environment to the social, and cultural changes of society in Algeria and his opportunity’s to trust the relation between the sports consumer available about the sports market and the sports consumer. as well as the positive indicators. This study was based on a sample that is estimated at 57 of manager in clubs to footballs and gym hall and others employments at youth and sport directorates for each of the states of Sétif . Chlef . And Medea The results revealed through the assumptions that he analyzed discussed them statistically and that were positive for all phrases and that were indicative Statistically. Where this study enabled to know the strengths and weaknesses in the feasibility of implementing the projects of sports institutions and how to move from competitive sport to competitive professional sports by constructed an economic theory in the sports field and this is to provide an incubating environment for investment for small and medium sports institutions